Validation of the KDIGO acute kidney injury criteria in a pediatric critical care population - Selewski, David T.; Cornell, Timothy T.; Heung, Michael; Troost, Jonathan P.; Ehrmann, Brett J.; Lombel, Rebecca M.; Blatt, Neal B.; Luckritz, Kera; Hieber, Sue; Gajarski, Robert; Kershaw, David B.; Shanley, Thomas P.; et al. (Intensive care medicine, 2014)
Purpose Acute kidney injury (AKI) occurs commonly in critically ill children and has been associated with increased mortality of up to 50 %. The Kidney Disease: Improving Global Outcomes (KDIGO) AKI working group has proposed a standardized definition of AKI. Utilizing routinely available clinical data, we evaluated the KDIGO AKI criteria and the relationship of AKI with relevant outcomes in a single center tertiary pediatric intensive care (PICU) and cardiac intensive care unit (CICU) population. Methods The University of Michigan Pediatric Critical Care Database was probed for all discharges from the pediatric intensive care and cardiac intensive care units between July 2011 and October 2013 ( N = 4,645). The KDIGO serum creatinine (SCr)-based criteria staged AKI with the modification that a minimum SCr of greater than 0.5 mg/dL was required to be classified as AKI. Exclusion: end-stage renal disease, new renal transplant, missing PRISM III data, or no measured Cr during intensive care unit (ICU) admission ( N = 1,636). Results AKI occurred in 737 (24.5 %, stage 1 = 193, stage 2 = 189, and stage 3 = 355) of 3,009 discharges (PICU N = 1,870, CICU N = 1,139) that included 2,415 patients. In multivariate analysis AKI was associated with increased ICU length of stay (LOS) in hours (stage I β = 42.2, p = 0.024, II β = 74.1, p = 0.003, III β = 215.8, p < 0.001). Multivariate analysis showed that AKI was associated with increased odds of ICU mortality (OR 3.4, 95 % CI 2.0–6.0) and increased length of mechanical ventilation among those requiring mechanical ventilation ( β = 2.3 days, p < 0.001). Conclusions Using the KDIGO criteria to define AKI, we observed a high prevalence of AKI among critically ill children. Worsening stages of AKI were associated with increased ICU LOS, and AKI was independently associated with prolonged mechanical ventilation and increased mortality. The KDIGO criteria describe clinically relevant AKI in a broad pediatric critical care population.